Association between obesity and vulvar cancer recurrence: an analysis of the AGO-CaRE-1 study. Issue 7 (28th May 2020) - Klapdor, Rudiger; Hillemanns, Peter; Wölber, Linn; Jückstock, Julia; Hilpert, Felix; de Gregorio, Nikolaus; Hasenburg, Annette; Sehouli, Jalid; Fürst, Sophie; Strauss, Hans; Baumann, Klaus; Thiel, Falk; et al.
Abstract : Objective: Obesity is associated with worse survival and an increased risk of relapse in several malignancies. The influence of obesity on vulvar cancer recurrence has not been previously described. The primary objective of this study was to evaluate the association between obesity and tumor recurrence in patients with vulvar cancer. Methods: This is an analysis of the AGO-CaRE-1 study. Patients diagnosed with squamous cell vulvar cancer (stage IB and higher), treated in 29 cancer centers between January 1998 and December 2008, were registered in a centralized database. The cohort was divided into two gropus depending on the body mass index (BMI) (<30 vs ≥30 kg/m²). Descriptive statistics, survival analyses, and multivariate Cox regression analyses were performed in order to evaluate the association between obesity and progression-free and overall survival. Results: In 849 (52.4%) of 1618 patients in the database, the BMI was documented. Patients were grouped according to their BMI (<30 vs ≥30 kg/m²). There were 621 patients with a BMI <30 kg/m² and 228 patients with a BMI ≥30 kg/m². Besides age, there was no difference in baseline variables (tumor diameter, depth of infiltration, tumor stage, nodal metastasis, tumor grade). Treatment variables (R0 resection, chemotherapy, radiotherapy, continuation of adjuvant therapy) did not differ between groups. However, patients with BMI ≥30 kg/m² underwent radical vulvectomy more often (61.1% vs 51.8%, p=0.04). During follow-up there was a higher recurrence rate in the group with BMI ≥30 kg/m² (43.4% vs 28.3%, p<0.01) due to an increased rate of local recurrences (33.3% vs 18.5%, p<0.01). There was a significantly shorter time to recurrence in obese patients on univariate analysis (BMI ≥30 kg/m² vs <30 kg/m²: 43.8 months (95% CI 23.3 to 64.3) vs 102.3 months (95% CI 72.6 to 131.9), p=0.001) and on multivariate Cox regression analysis (HR 1.94 (95% CI 1.4 to 2.8), p<0.001). Conclusions: In this study a BMI ≥30 kg/m² was associated with a shorter time to recurrence in patients with vulvar cancer and this was mainly attributed to a higher risk of local recurrence.